10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Recent research concludes that health improvements in the 20th century caused a surge in social conflict by accelerating population growth. Rationalized by Malthusian population dynamics, this indicates a potential trade-off for world-wide health initiatives, especially in conflict-prone regions. Here, we re-investigate this question with fine-grained contemporary data. After conceptualizing the chain of mechanisms that links health-driven population growth to conflicts, we address the question whether health improvements cause Malthusian conflict dynamics in 50 countries in Africa over the period 1990-2017. The analysis combines the massive worldwide roll-out of antiretroviral therapy (ART) for HIV-positive individuals during the early 2000s with local variation in treatment potential before the onset of this expansion. We find that the deployment of ART has indeed led to a demographic expansion. In sharp contrast to the literature on Malthusian dynamics, we find that this health-induced population growth has not resulted in a surge of conflict measured in terms of (small or medium scale) social violence or large scale armed conflict. For armed conflict, we find no effects, whereas for social violence we detect a reduction. The findings substantially qualify existing evidence by documenting that public health provision and medical innovation, while entailing accelerated population growth, do not necessarily induce Malthusian conflict dynamics, but rather may entail a "double dividend" in terms of health improvements and a reduction in conflicts.